Schistosoma mansoni Fibroblast Growth Factor Receptor A Orchestrates Multiple Functions in Schistosome Biology and in the Host-Parasite Interplay - Du, Xiaofeng; McManus, Donald P.; Fogarty, Conor E.; Jones, Malcolm K.; You, Hong (Frontiers in Immunology, 2022)
Stem cells play significant roles in driving the complex life cycle of Schistosoma mansoni. Fibroblast growth factor (FGF) receptor A (SmFGFRA) iis essential for maintaining the integrity of schistosome stem cells. Using immunolocalization, we demonstrated that SmFGFRA was distributed abundantly in germinal/stem cells of different S. mansoni life stages including eggs, miracidia, cercariae, schistosomula and adult worms. Indeed, SmFGFRA was also localized amply in embryonic cells and in the perinuclear region of immature eggs; von Lichtenberg’s layer and the neural mass of mature eggs; the ciliated surface and neural mass of miracidia; the tegument cytosol of cercariae, schistosomula and adult worms; and was present in abundance in the testis and vitellaria of adult worms of S. mansoni. The distribution pattern of SmFGFRA illustrates the importance of this molecule in maintaining stem cells, development of the nervous and reproductive system of schistosomes, and in the host-parasite interplay. We showed SmFGFRA can bind human FGFs, activating the mitogen activated protein kinase (MAPK) pathway of adult worms in vitro. Inhibition of FGF signaling by the specific tyrosine kinase inhibitor BIBF 1120 significantly reduced egg hatching ability and affected the behavior of miracidia hatched from the treated eggs, emphasizing the importance of FGF signaling in driving the life cycle of S. mansoni. Our findings provide increased understanding of the complex schistosome life cycle and host-parasite interactions, indicating components of the FGF signaling pathway may represent promising targets for developing new interventions against schistosomiasis.